Prevalence of Vibrio cholerae in human-, poultry-, animal excreta and compost samples (Stamford Journal of Microbiology, 2013)
Transmission of Vibrio cholerae might take place in water bodies that often undergo contamination with human-, poultry- and animal excreta. In the present study, wastes from all three categories were analyzed microbiologically. Twelve poultry excreta samples, 12 human excreta samples and 12 cowdung samples were examined for the presence of V. cholerae. High prevalence of V. cholerae was found in each of the samples and the highest prevalence was observed for human excreta samples (2.2x108 cfu/g). Besides, 24 compost samples, which were prepared using human feces, were tested. The load of V. cholerae was found lower in the compost samples (from 0 to 2.2x103 cfu/g) than that of the excreta samples. The study of antibiogram showed that all the isolates were resistant against ampicillin, erythromycin, tetracycline, chloramphenicol, nalidixic acid, meropenem and cefotaxime. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15213 Stamford Journal of Microbiology, Vol.2(1) 2012: 38-41